Formation of self-organized anisotropic polymer structures by confined dynamic instability - Kwon, SJ (AMER INST PHYSICS, 2006)
We report on the formation of self-organized anisotropic structures of the polymer thin films induced by the wave interaction-driven dynamic instability confined by corrugated elastomeric molds. In the initial stage of the morphological instability, self-organized anisotropic structures such as a regularly undulated surface wave pattern formed on the ridge followed by the formation of a highly ordered array of droplets on the wall and a surface wave on the groove. The self-organization in the initial stage is dominated by the formation of the surface wave on the ridge accompanying a period of half the first harmonic wavelength of the mold corrugation. In the final stage of the instability, undulated polymer structure on the ridge is transformed into a periodic array of droplets with the first harmonic wavelength of the mold corrugation, while the undulation in the polymer layer on the groove is nearly sustained. The self-organized anisotropic polymer structures can provide simpler methods of fabricating complicated three-dimensional polymeric structures. (c) 2006 American Institute of Physics.
Keywords: THIN-FILMS; DEFORMATION; SURFACE